2019
DOI: 10.1016/j.ceramint.2019.05.105
|View full text |Cite
|
Sign up to set email alerts
|

Facile green synthesis of ytrium-doped BiFeO3 with highly efficient photocatalytic degradation towards methylene blue

Abstract: Bismuth ferrite (BiFeO 3) is considered as one of the most promising materials in the field of multiferroics with great potentials in photocatalysis due to their excellent properties of relatively small band gap, stable structures, and low cost. In this work, a facile green route was successfully used for the fabrication of high-purity yttriumdoped and undoped bismuth ferrite (BiFeO 3) nanoparticles. κ-carrageenan seaweed was used as a biotemplate for the construction of the material. The obtained products wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…15. 185 Also, a significant effect of 1% dopant concentration in pure BFO is demonstrated with almost 100% efficiency in the first phase.…”
Section: Methods To Enhance the Photocatalytic Activity For Bismuth F...mentioning
confidence: 93%
“…15. 185 Also, a significant effect of 1% dopant concentration in pure BFO is demonstrated with almost 100% efficiency in the first phase.…”
Section: Methods To Enhance the Photocatalytic Activity For Bismuth F...mentioning
confidence: 93%
“…In addition, the effects of Ce doping on the morphology and magnetic characteristics have been investigated [8][9][10]. It has been reported that the doping of rare-earth ions such as Gd and Ce onto BFO shows enhanced photocatalytic degradation of RhB [11][12][13][14][15][16][17][18][19][20][21]. In this report BFO and Bi1−xGdxFe1−yCeyO3 (where x = 0.1 & y = 0.05, 0.1 and 0.15) samples were synthesized by sol-gel method.…”
Section: Introductionmentioning
confidence: 89%
“…Thus, 1% yttrium doped BiFeO 3 has better degradation efficiency of 97.6% at this surface area. 74 The saturation magnetization of the material has been increased by dopants and co-dopants in the material. The increased saturation 19.…”
Section: Oh Dye Dye Oxidation E Dye Dye Reductionmentioning
confidence: 99%